Using phenomenal concepts to explain away the intuition of contingency - Shea, N (Taylor and Francis, 2012)
Humans can think about their conscious experiences using a special class of ‘phenomenal’ concepts. Psycho-physical identity statements formulated using phenomenal concepts appear to be contingent. Kripke argued that this intuited contingency could not be explained away, in contrast to ordinary theoretical identities where it can. If the contingency is real, property dualism follows. Physicalists have attempted to answer this challenge by pointing to special features of phenomenal concepts that explain the intuition of contingency. However no physicalist account of their distinguishing features has proven to be satisfactory. Leading accounts rely on there being a phenomenological difference between tokening a physical-functional concept and tokening a phenomenal concept. This paper shows that existing psychological data undermine that claim. The paper goes on to suggest that the recalcitrance of the intuition of contingency may instead by explained by the limited means people typically have for applying their phenomenal concepts. Ways of testing that suggestion empirically are proposed.